Penerapan Model Pembeajaran Two Stay Two Stray Pada Materi Struktur Dan Fungsi Tumbuhan - Oktaviani, Alda; St. Humaerah Syarif (Program Studi Tadris IPA IAIN Parepare, 2025)
This study aims to improve the science learning outcomes of students, which have been low due to difficulties in understanding the lesson material and a lack of engagement in the learning process. This issue stems from the selection of a learning model that is considered inappropriate. Therefore, this study applies the Two Stay Two Stray learning model to enhance students' learning outcomes. The research method used is Classroom Action Research (CAR), conducted in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. The subjects of the study are the eighth-grade students of class VIII.2 at SMP Negeri 6 Parepare. The instruments used in this study are tests and observation sheets.The observation results during the pre-action phase indicate that most students had low learning outcomes, with an average score of 49.52. Only 2 students achieved mastery, while 19 other students had not mastered the material, with a classical mastery rate of 9.52%. In cycle 1, the average score increased to 76.9, with 17 students achieving mastery and 4 students still not mastering, resulting in a classical mastery rate of 80.95%. In cycle 2, the average score reached 90.95, and the classical mastery rate reached 100%. These results show that all students achieved a mastery score above 75, with a classical mastery rate above 85%, indicating that this cycle has reached optimal results.